2004
DOI: 10.1007/s00403-004-0533-9
|View full text |Cite
|
Sign up to set email alerts
|

The formation of wrinkles caused by transition of keratin intermediate filaments after repetitive UVB exposure

Abstract: It has been reported that the formation of wrinkles involves changes in the elastic properties of the dermis due to the denaturation of elastic fibers. Several studies have shown that the hydration condition of the stratum corneum is also important in wrinkle formation. It is, however, still unclear how the stratum corneum contributes to wrinkle formation. Here we investigated the relationship between the formation of wrinkles and changes in the physical properties and condition of the skin after repetitive ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…[1][2][3] Skin photodamage is physiologically correlated with several alterations including the increase and disorganization of elastic fibers and the reduction of collagens in the dermal extracellular matrix 4 -11 and the increase of keratin contents and the deterioration of keratin intermediate filaments (KIFs) in the epidermis. [12][13][14] Elastic fibers are age-dependent-decreasing dermal extracellular matrix that respond primarily to the fibrous mechanism controlling cutaneous elasticity. 4,5,15,16 The accumulation of dystrophic elastotic material in the reticular dermis, referred to as solar elastosis, is commonly observed in photoaged skin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Skin photodamage is physiologically correlated with several alterations including the increase and disorganization of elastic fibers and the reduction of collagens in the dermal extracellular matrix 4 -11 and the increase of keratin contents and the deterioration of keratin intermediate filaments (KIFs) in the epidermis. [12][13][14] Elastic fibers are age-dependent-decreasing dermal extracellular matrix that respond primarily to the fibrous mechanism controlling cutaneous elasticity. 4,5,15,16 The accumulation of dystrophic elastotic material in the reticular dermis, referred to as solar elastosis, is commonly observed in photoaged skin.…”
mentioning
confidence: 99%
“…38 -41 In hairless mice, a repeated low-dose UV exposure has been reported to deteriorate KIFs and induce the expression of epithelial keratins (K1, K5, and K10), resulting in the loss of skin elasticity and eventually initiating wrinkled skin, consistent with previous reports demonstrating no causal relationship between wrinkle formation and dermal changes. [12][13][14]42,43 Many studies of skin photoaging have been conducted using animal models and human skin substitute. The results may be misleading because of inferior architecture, such as the relative thin epidermal layer and compromised barrier function.…”
mentioning
confidence: 99%
“…Various systemic agents in the form of antioxidants, vitamins and minerals, designated as systemic sunscreens, have emerged as new photo-protective measure. The main goals of sunscreens are to protect against UVB radiation and longwavelength UVA radiation, scavenge ROS, activate cellular repair systems, including DNA repair [2,3].…”
Section: Sunscreensmentioning
confidence: 99%
“…5 Furthermore, we have shown that the IL-20 receptors IL20Ra and IL-20Rb are expressed on human dermal fibroblasts. 6 Therefore, we hypothesize that solar light-induced IL-20 production in keratinocytes might contribute to aging processes in the dermis.…”
Section: Introductionmentioning
confidence: 99%
“…38 Intriguingly, many of these changes have also been described for UV-irradiated mouse and human skin. 5 Recently, we have shown that UVB irradiation enhances IL-20 expression in human keratinocytes, and the IL-20 heterodimeric receptor complex consisting of the subunit IL20R1 and IL20R2 is expressed on NHDFs. 6 These findings suggest a role of this novel ligand in dermal photoaging.…”
mentioning
confidence: 99%